HUBUNGAN ANEMIA DENGAN STATUS GIZI PADA REMAJA PUTRI - Roos Arum Parasdia; Puspa Sari Sari; Ari Indra Susanti; Merry Widjayanti (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2017)
Anemia can cause a risk to adolescent girls both long term and in the short term. One of the factors influence anemia in adolescents is nutrition status. This study aims to determine of anemia in adolescent with nutritional status in adolescent girls The Design of this study is cross sectional. The sample of this study is 84 adolesent girls, people was selected by simple random sampling technique from all student at class x ech high school on 2-3 August 2016. hemoglobin levels was checked by a digital, nutritional status examination of weight and height. Data were analyzed with univariate and bivariate chi square. The results of the study shows that the prevalence of anemia in adolescent is 45.2%, nutritional status underwieght is 14,3%. There is no relationship between anemia with nutrisional status (p-value=0,649). The conclusion of this research is the prevalence of anemia is still high,and there was no significant association between anemia and nutritisional status.